Pre-diagnosis blood glucose and prognosis in women with breast cancer. Issue 1 (December 2016) - Monzavi-Karbassi, Behjatolah; Gentry, Rhonda; Kaur, Varinder; Siegel, Eric; Jousheghany, Fariba; Medarametla, Srikanth; Fuhrman, Barbara; Safar, A.; Hutchins, Laura; Kieber-Emmons, Thomas
Abstract Background The effect of moderately elevated blood glucose levels among non-diabetic subjects on cancer prognosis is not well described. The goal of this study was to examine the association of elevated random blood glucose (RBG) levels in non-diabetic breast cancer patients with overall survival (OS) and time to tumor recurrence (TTR). Results Forty-nine deaths and 32 recurrences occurred among 148 eligible study subjects during 855.44 person-years of follow-up, with median follow-up of 5.97 years. We observed that patients with elevated RBG levels experienced significantly shorter OS (hazard ratio [HR], 3.01; 95 % confidence interval [CI] (1.70–5.33);P  < 0.001) and shorter TTR (HR, 2.08; CI (1.04–4.16);P  = 0.04) as compared to patients with non-elevated RBG levels. After controlling for tumor grade, tumor stage, race, and BMI, elevated RBG continued to display high and statistically significant association with shorter OS (HR, 3.50; CI (1.87–6.54);P <  0.001). Adjustment for age, race, and BMI strengthened HR of RBG for TTR. The association of RGB with TTR lost its borderline statistical significance upon controlling for both tumor grade and stage. Conclusions The data suggest that elevated blood glucose is associated with poor prognosis of breast cancer patients. Given the potential clinical implication, these findings warrant further investigation.